2021
DOI: 10.1021/acscatal.1c02102
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Metal Shell as an Effective Iron Oxide Modifier for Redox-Based Hydrogen Production at Intermediate Temperatures

Abstract: This study reports molten metals (bismuth, indium, and tin) as effective modifiers for iron-based redox catalysts in the context of chemical loopingbased hydrogen production at intermediate temperatures (450−650 °C) from lowcalorific-value waste gas (e.g., blast furnace gas). The effects of the bismuth promoter on both the surface and bulk properties of iron oxides were studied in detail. Transmission electron microscopy and energy-dispersive spectroscopy (TEM-EDS), low-energy ion scattering (LEIS), Raman spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Liquid metals would be further developed in catalysis, 17 catalytic hydrogen production, 18 and catalytic atom transfer of free radicals. 19 At room temperature, a LM base method is proposed for the catalytically assisted deposition and graphitization of molybdenum dioxide (MoO 2 ) (Fig.…”
Section: Research Progress Of Liquid Metal Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid metals would be further developed in catalysis, 17 catalytic hydrogen production, 18 and catalytic atom transfer of free radicals. 19 At room temperature, a LM base method is proposed for the catalytically assisted deposition and graphitization of molybdenum dioxide (MoO 2 ) (Fig.…”
Section: Research Progress Of Liquid Metal Catalystsmentioning
confidence: 99%
“…The chemical cycling of LMs (Bi, In, and Ti) from low calo-ric value exhaust gases (e.g., blast furnace gas) as effective modiers for iron-based redox catalysts has been investigated at moderate temperatures (450-650 °C). 18 The bismuth modier forms a coating layer on the Fe oxide matrix and has better anticoking performance than the Fe oxides supported by La 0.8 Sr 0.2 FeO 3 and Ce 0.9 GD 0.1 O 2 . In the cyclic redox reaction at 550 °C, the sintering resistance and redox activity of bismuth-modied samples were also improved, and the oxygen capacity was 4 times higher than that of the original Fe 2 O 3 (28.9 vs. 6.4 wt%).…”
Section: Research Progress Of Liquid Metal Catalystsmentioning
confidence: 99%
“…20,23 Iron/iron oxide redox pairs are commonly used as the redox catalyst. [25][26][27][28][29][30][31][32][33] However, studies have shown that they generally lead to low syngas selectivity and CO 2 conversion. 25,34,35 On the other hand, mixing Fe with other metal oxides has been shown to improve redox properties.…”
Section: Introductionmentioning
confidence: 99%
“…[54][55][56] Although tremendous efforts have been made in developing RCs, their optimization still largely relies on heuristics and trial-and-error. Meanwhile, the emergence of mixed oxides has expanded the design space for RCs 28,[57][58][59] thus making it impractical to screen out the promising RCs given the infinitely many possible compositions of mixed oxides. Therefore, effective computational tools are highly desirable to narrow down the design space for RC development and optimization.…”
Section: Introductionmentioning
confidence: 99%
“…They are usually low-melting-point alloys (−19 • C) and have high flexibility, variable shape, high electrical conductivity, high thermal conductivity, liquidity, high surface tension and flexibility, nontoxicity, and other characteristics [4]. Liquid metal photocatalysis was based on non-toxic gallium-based alloys [5,6]. Catalysts prepared by liquid metals and their compounds have great potential for starting, accelerating chemical reactions, and improving product yield [7,8].…”
Section: Introductionmentioning
confidence: 99%